Numerical study on power battery thermal management system based on heat pipe technology - Meng Zheng; Ye Liu; Zheshu Ma; Yanju Li; Dongxu Li; Zhanghao Lu; Hanlin Song; Xinjia Guo; Wei Shao (Energy Reports, 2023)
In the present work, a power battery pack and a novel thermal management system (TMS) based on the tubular heat pipe (THP) technology are designed according to the parameters of a pure electric light truck and battery. The TMS consists of THPs, power batteries, cooling plates, fins, and equivalent thermal conductivity is used to characterize the excellent thermal conductivity of THP. The heat generation rate of the battery at different discharge rates is obtained by establishing a multi-scale electrochemical–thermal coupling model, which accuracy is verified by the experiment. A multi-physics field coupling model is built to the thermal management system designed for the study. The results show that the battery temperature is higher when the battery is far from the THP in the cooling plate, and the maximum temperature reaches 35.6 °C at 1 C. Furthermore, the temperature difference between batteries is proportional to the discharge rate, and the maximum temperature difference reaches 7 °C at 2 C. The change in inlet temperature and wind speed can only restrain the temperature rise, while the temperature difference of the battery module is always 3.2 °C. When a fin spacing of 3 mm is chosen, the best temperature uniformity of the battery module is achieved at this time. The use of the multi-scale multi-physics field coupling analysis method in BTMS with heat pipes can be used as a reference for future numerical simulations of the same type.